176k views
21 votes
-4-(3) =
3+(-5) =
4+6=
-5-9=
-4+(-9) =​

User Stacey
by
5.6k points

2 Answers

5 votes

Explanation:

-4-(3)=-7

step two

3+(-5)=-2

step three

4+6=10

step four

-5-9=-14

step five

-4+(-9)=-13

User Kkocabiyik
by
5.2k points
2 votes

Answer:

a) -4 - ( 3) = - 7

b) 3 + ( -5) = 3 - 5 = -2

c) 4 + 6 = 10

d) -5 -9 = - 14

e) -4 + ( -9) = -4 -9 = - 13...

User David Rodrigues
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.